Behavior Determining the Use of Internet Communication Technology: Facility Conditions and Performance Expectations - Ni Putu Cempaka Dharmadewi Atmaja; Ni Made Dwi Puspitawati (Journal of International Conference Proceedings (JICP), 2020)
The Covid 19 pandemic has made internet-based communication technology the main thing to communicate effectively in the world of education. The purpose of this study was to determine the effect of facility conditions and performance expectations on the behavior of using communication technology (actual use and use intention. Sampling using the purposive sampling method. Distribution of questionnaires was conducted to 100 students who are still effective using internet-based communication technology in lectures. The data analysis tool uses Structural Equation Modeling (SEM) with AMOS version 22. The results of this study state that Performance expectations are a construct that has a significant effect on intention use and actual use, while facility conditions only affect intention use and have no significant effect on actual use. The implication of this research is that the teachers and students must communicate effectively in the choice of technology in order to increase student expectations to improve their academic abilities.